'A STUBBORN, INTRACTABLE BODY'1: RESISTANCE TO THE WORKHOUSE IN WALES, 1834–1877. (October 2014) - Evans, Megan; Jones, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Despite a recognition that Welsh poor law authorities were less than welcoming to many of the strictures of the Poor Law Amendment Act in 1834, historians have tended to downplay the importance of their resistance in the context of the wider anti-poor law 'movement' across England and Wales. Instead, a general consensus has arisen that Welsh boards of guardians tended to resist the New Poor Law on the grounds of financial expediency or provincial insularity, rather than because of any ideological or humanitarian hostility towards its provisions. This article presents compelling evidence that this consensus is quite wrong, and demonstrates in turn that, not only were Welsh guardians far more successful in their resistance to the new workhouse regime even the most recalcitrant English unions, but that that resistance was founded upon a long-standing and coherent antipathy to the punitive nature of the workhouse as an institution, rather than simply being founded on short-term financial or practical considerations.